The key success factors influencing teacher ethics for higher education institutions in minority areas of Sichuan province - Qiao, Xiaohu; Noichun, Nuntiya; Boonphadung, Suttipong (Edelweiss Applied Science and Technology, 2024)
To explore in-depth factors affecting teacher ethics for higher education institutions in ethnic areas of Sichuan and to improve the level of teacher ethics and to provide a talent base for the high-quality development of higher education. Teacher ethics for higher education institutions is a synthesis of ethical concepts, ethical qualities, and behavioral norms that teachers should follow in the course of their professional work. This study constructed a structural equation model of teacher ethics and further analyzed the influence of ethical climate, professional identity, and psychological contract on teacher ethics. This study used SPSS and AMOS software to process and analyze 400 questionnaire data. Ethical climate, professional identity, and psychological contract all have a significant positive effect on teacher ethics. Ethical climate and psychological contract both have a significant positive effect on professional identity. Professional identity plays a significant mediating effect between ethical climate and teacher ethics, psychological contract and teacher ethics. This study has constructed the index system of the influencing factors of teacher ethics to understand the influencing mechanism of teacher ethics of higher education institutions in the ethnic areas of Sichuan. It enriches the research results in the field of teacher ethics in higher education institutions.